2016
DOI: 10.1007/s13201-016-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact assessment on hydrology of a small watershed using semi-distributed model

Abstract: This study is an attempt to quantify the impact of climate change on the hydrology of Armur watershed in Godavari river basin, India. A GIS-based semi-distributed hydrological model, soil and water assessment tool (SWAT) has been employed to estimate the water balance components on the basis of unique combinations of slope, soil and land cover classes for the base line and future climate scenarios (2071-2100). Sensitivity analysis of the model has been performed to identify the most critical parameters of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 33 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…Watershed models, such as the Soil and Water Assessment Tool (SWAT) [27], coupled with regional climate models (RCM) have been used to assess the impacts of CC on the water balance components (WBCs) of watersheds [27,28]. There is a number of hydrological modeling and climate change studies on the leeward side of Oahu Island [19,21,22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Watershed models, such as the Soil and Water Assessment Tool (SWAT) [27], coupled with regional climate models (RCM) have been used to assess the impacts of CC on the water balance components (WBCs) of watersheds [27,28]. There is a number of hydrological modeling and climate change studies on the leeward side of Oahu Island [19,21,22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a 25% increase in rainfall leads to a 50% increase in the river discharge over Upper Blue Nile Basin. The increase in streamflow due to rainfall increment was also discussed by Pandey et al (2017); they revealed that a 28% increase in annual rainfall may result in streamflow increased by approximately 49% from their study in the Armur watershed in Godavari river basin, India. The decrease in streamflow during the rainy season associated with the rainfall reduction corresponds with the findings of Worqlul et al (2018) in the Upper Blue Nile Basin, Ethiopia.…”
Section: Discussionmentioning
confidence: 94%
“…Andreini et al [62] concluded that the large changes that occur in surface runoff correspond to a lesser change in precipitation. Additionally, in India, Pandey et al [63] quantified the climate change impact (2071-2100) in the Armur basin using SWAT, suggesting that evapotranspiration and water production will increase 28% and 49%, respectively.…”
Section: Discussionmentioning
confidence: 99%